Desertification Around the Thar-A Geomorphological Interpretation - Ghosh, Bimal; Singh, Surendra; Kar, Amal (Annals of Arid Zone, 2016)
Desertification around the peripheries of the Thar is still a controversial topic. The authors’ studies on the different geomorphic aspects of the Thar desert in Rajasthan indicate, however, that the desert is not expanding towards its eastern peripheries at present although there are evidence of more than one climatic fluctuations and consequent expansion and contraction of the desert during the past. The present study also shows that there are indications of recent shrinkage of the desert in a real extent. However, the unscientific exploitation of resources by man have resulted in wind depositional and salinity hazards and is causing serious ecological imbalances.